IN SILICO ANALYSIS OF ANTIFUNGAL POTENTIAL AND PHARMACOKINETIC CHARACTERISTICS OF SHALLOT (Allium cepa L.) SECONDARY METABOLITES USING PASS ONLINE AND SWISSADME: ANALISIS IN SILICO POTENSI ANTIFUNGI DAN KARAKTERISTIK FARMAKOKINETIK METABOLIT SEKUNDER BAWANG MERAH (Allium cepa L.) MENGGUNAKAN PASS ONLINE DAN SWISSADME - Ahdilan Juliansyah; Rahadatul Aisy Wafadhiyanti Indrapaslah; Erwandi Erwandi; Hikmal Hikmal; Juliadi Nur Rahim; Dodi Iskandar (PT. ROCE WISDOM ACEH, 2026)
Shallot (Allium cepa L.) contains various secondary metabolites with potential biological activities, including antifungal activity. This study aimed to evaluate the antifungal potential and pharmacokinetic characteristics of secondary metabolites from shallot using in silico approaches with PASS Online and SwissADME. PASS Online analysis demonstrated that all identified compounds possessed potential antifungal activity with varying Probability of Activity (Pa) values. Among the compounds, (+)-Dihydroeleutherinol showed the highest antifungal potential with a Pa value of 0.608, followed by (-)-3-[2-(Acetyloxy)propyl]-2-hydroxy-8-methoxy-1,4-naphthoquinone and (-)-Hongconin with Pa values of 0.599 and 0.594, respectively. The antifungal activity of these compounds is associated with their ability to disrupt fungal cell membranes, inhibit cell wall synthesis, and induce oxidative stress via the formation of reactive oxygen species (ROS). SwissADME analysis indicated that all compounds exhibited favorable pharmacokinetic and physicochemical profiles, including high water solubility, balanced lipophilicity, and acceptable bioavailability scores ranging from 0.55 to 0.56. Drug-likeness analysis further revealed that all compounds complied with Lipinski, Ghose, Veber, Egan, and Muegge rules, indicating good oral absorption potential and membrane permeability. In addition, physicochemical property analysis showed that all compounds had molecular weights below 500 g/mol, low topological polar surface area (TPSA), balanced hydrogen-bonding properties, and moderate molecular flexibility, which are important characteristics for drug development. Compounds such as (+)-Eleutherin, (-)-Isoeleutherin, and (+)-Dihydroeleutherinol demonstrated particularly promising profiles due to their balanced physicochemical and pharmacokinetic properties. Overall, the combined PASS Online and SwissADME analyses suggest that shallot secondary metabolites have strong potential as natural antifungal agents. However, further in vitro and in vivo studies are required to validate their biological activity, safety, toxicity, and mechanisms of action against pathogenic fungi.